(untitled) (Minerva, 2020)
This paper analyses some parallels between classical Rhetoric and modern Pragmatics. Both disciplines focus on communicative interaction. The paper offers a comparison between rhetorical decorum and three contemporary pragmatic theories on the principles of cooperation, politeness, and relevance. After identifying some problematic aspects, a possible contribution from Classical Rhetoric seems reasonable, especially when taking into consideration that the rhetorical concept of decorum, lacking an equivalent in the field of Pragmatics, might be useful as a unifying mechanism.